Microstructure analysis of "iron spots" on Qinghua porcelain from Jingdezhen imperial kiln. Issue 2 (February 2023) - Wang, Wenxuan; Sciau, Philippe; Zhu, Jian; Jiang, Jianxin; Wen, Rui; Brunet, Magali
Abstract: "Iron spots" as a characteristic of early Qinghua porcelain is closely related to cobalt pigment and manufacturing technology. However, the microstructure of "iron spots" has not been fully investigated. Seventeen Qinghua samples with "iron spot" excavated in Jingdezhen imperial kiln were observed under stereomicroscope and SEM. Then, four representative sherds were systematically analyzed using FIB-TEM-EDX. Some ferrite solid solutions (CoFe2 O4 -Fe3 O4 and Mn3 O4 -MnFe2 O4 -Fe3 O4 ) are identified. CaFeAlSiO6 and Na2 Al2 Si2 O6 -CaAl2 Si2 O6 continuous solid solutions, as the main crystallites of "iron spot" are first reported. Moreover, we proposed that the dramatic increase of Fe or Mn in "iron spot" is caused by the source or formular change of cobalt pigment. Varieties of morphologies and species of the "iron spots" in Hongwu and Xuande reign implies that technology is under a transition period for adapting new formular, which provide a new perspective to discuss the use of cobalt pigments and technology development of Qinghua porcelain.